The Employment of Low-Skilled Men: Evidence from the Labour Force Survey, 1976-2013 - Liu, Jingwei (Université d'Ottawa | University of Ottawa, 2015)
Using Canadian Labour Force data from 1976 to 2013, this paper explores why the employment rate of the low-skilled males has been declining from 87% to 76%. I first provide a detailed characterization of how low-skilled males' employment rate has changed over time, and then explore the sources of change by looking at the labour force participation of the wives of these low-skilled men, considering females' employment changes is the main reason. I find that the low-skilled males employment rate declines substantially over 1976 to 2013 period. In addition, the percentage of low-skilled males who decide to leave the labour force has increased substantially, and so has their wives' employment rate. I therefore would have expected that the females' increasing labour force participation would have been an important explanation for the change in the employment of low-skilled males. However, the regression results show the opposite. I find that married low-skilled males who have wives that work will be more likely to be working, and less likely to leave the labour force.